Astrocytic Lrp4 (Low-Density Lipoprotein Receptor–Related Protein 4) Contributes to Ischemia-Induced Brain Injury by Regulating ATP Release and Adenosine-A2AR (Adenosine A2A Receptor) Signaling. Issue 1 (January 2018) - Ye, Xin-Chun; Hu, Jin-Xia; Li, Lei; Li, Qiang; Tang, Fu-Lei; Lin, Sen; Sun, Dong; Sun, Xiang-Dong; Cui, Gui-Yun; Mei, Lin; Xiong, Wen-Cheng
Abstract : Background and Purpose—: Lrp4 (low-density lipoprotein receptor–related protein 4) is predominantly expressed in astrocytes, where it regulates glutamatergic neurotransmission by suppressing ATP release. Here, we investigated Lrp4's function in ischemia/stroke-induced brain injury response, which includes glutamate-induced neuronal death and reactive astrogliosis. Methods—: The brain-specific Lrp4 conditional knockout mice (Lrp4 GFAP-Cre ), astrocytic-specific Lrp4 conditional knockout mice (Lrp4 GFAP-creER ), and their control mice (Lrp4 f/f ) were subjected to photothrombotic ischemia and the transient middle cerebral artery occlusion. After ischemia/stroke, mice or their brain samples were subjected to behavior tests, brain histology, immunofluorescence staining, Western blot, and quantitative real-time polymerase chain reaction. In addition, primary astrocytes and neurons were cocultured with or without oxygen and glucose deprivation and in the presence or absence of the antagonist for adenosine-A2A R (adenosine A2A receptor) or ATP-P2X7R (P2X purinoceptor 7) signaling. Gliotransmitters, such as glutamate, D-serine, ATP, and adenosine, in the condition medium of cultured astrocytes were also measured. Results—: Lrp4, largely expressed in astrocytes, was increased in response to ischemia/stroke. Both Lrp4 GFAP-Cre and Lrp4 GFAP-creER mice showed less brain injury, including reduced neuronal death, and impaired reactive astrogliosis. Mechanistically, Lrp4 conditional knockout in astrocytes increased ATP release and the production of ATP derivative, adenosine, which were further elevated by oxygen and glucose deprivation. Pharmacological inhibition of ATP-P2 X7 R or adenosine-A2A R signaling diminished Lrp4 GFAP-creER 's protective effect. Conclusions—: The astrocytic Lrp4 plays an important role in ischemic brain injury response. Lrp4 deficiency in astrocytes seems to be protective in response to ischemic brain injury, likely because of the increased ATP release and adenosine-A2A R signaling. Abstract : Supplemental Digital Content is available in the text.